2015
DOI: 10.1159/000368746
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carvedilol on B-Type Natriuretic Peptide and Cardiac Function in Patients with Heart Failure and Persistent Atrial Fibrillation

Abstract: Objectives: We sought to determine the relationship between changes in natriuretic peptides and symptoms as a consequence of introducing beta-blocker therapy, in patients with chronic heart failure (CHF) and persistent atrial fibrillation (AF). Methods: In a randomised, double-blind, placebo-controlled study involving 47 patients with CHF and persistent AF (mean age 68 years and 62% men), we analysed the individual change (Δ) in B-type natriuretic peptide (BNP) level to the introduction of carvedilol (titrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…A larger proportion of our HHF patients may have had reduced EF possibly because of late presentation and advanced disease at the time of presentation. Khand et al 46 reported that dual therapy with carvedilol and digoxin among patients with AF and chronic HF resulted in improved NYHA class and median ventricular rate among other factors as compared with use of digoxin alone. This may imply that a more aggressive approach toward treating AF among HF patients may bring about reduction in ventricular rate, improvement in NYHA class, and possibly a better outcome among HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…A larger proportion of our HHF patients may have had reduced EF possibly because of late presentation and advanced disease at the time of presentation. Khand et al 46 reported that dual therapy with carvedilol and digoxin among patients with AF and chronic HF resulted in improved NYHA class and median ventricular rate among other factors as compared with use of digoxin alone. This may imply that a more aggressive approach toward treating AF among HF patients may bring about reduction in ventricular rate, improvement in NYHA class, and possibly a better outcome among HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a large prospective registry of AF patients in the United States, there was no increase in mortality or hospitalisation in patients using digoxin, with or without HF (55). A single RCT of 47 patients has examined digoxin and beta-blockers in patients with HFrEF and persistent AF (56). Double-blinded withdrawal of digoxin led to a decline in LVEF and increase in BNP, although the size of the trial limits further conclusions.…”
Section: Concomitant Heart Failure and Atrial Fibrillationmentioning
confidence: 99%
“…Due to an unstable TATAAT sequence and faster mRNA transcription, BNP can be instantaneously synthesized; hence, BNP can directly reflect heart chamber function and the severity of heart chamber dysfunction (Khand et al, 2015). NO also exhibits cytotoxicity and acts as an inflammatory mediator.…”
Section: Discussionmentioning
confidence: 99%